Modeling precipitation kinetics in multicomponent alloys during deformation - Bonvalet Rolland, Manon; Borgenstam, Annika (Frontiers in Materials, 2022)
A new mean-field modelling tool is developed to correctly tackle the problem of precipitation during deformation. The model is an expansion of a previously developed Langer-Schwartz-Kampmann-Wagner precipitation modelling approach for multicomponent alloys. The latter is now integrated together with the Thermo-Calc software and with physically-based equations describing the evolution of the dislocation density during hot-working. New equations for the nucleation barrier and the critical size have also been added to correctly simulate the early stages of precipitation. The model is applied to hot-compression tests for which experimental information was available. The model shows the importance to account for the overall precipitation kinetics, and not only for constant values of the precipitate volume fraction or size, to investigate the mechanical property evolution. This is due to a complex interplay between the defects and the precipitates evolution driven by a competition between thermodynamics and kinetics. Finally, it is highlighted how the strain rate that is employed affect the final microstructure of the material.